1991
DOI: 10.1007/bf00918645
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane-induced neutrophil adhesion to pulmonary microvascular and aortic endothelium is regulated by CD18

Abstract: Thromboxane (Tx) A2 generation and subsequent selective pulmonary sequestration of neutrophils (PMNs) is characteristic of several forms of the adult respiratory distress syndrome (ARDS). Therefore, we examined PMN-dependent adhesion to cultured pulmonary microvessel and aortic endothelium (EC) in response to U46,619 (Tx mimic). Nonstimulated PMNs were two fold more adherent to pulmonary microvessel EC than to aortic EC (P less than 0.01). PMN pretreatment with Tx mimic (10(-6) M) increased adhesion to both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 45 publications
1
16
0
2
Order By: Relevance
“…In the present study, subcutaneous administration of ONO-1301 significantly attenuated bleomycin-induced increases in total cell counts, neutrophil counts, and total protein level in BAL fluid. Earlier studies have shown that TXA 2 acts as a proinflammatory mediator via enhancement of pulmonary vascular permeability (18,24) and neutrophil adhesion (33). In the present study, TXB 2 , a stable metabolite of TXA 2 , was significantly increased after bleomycin injection, which is consistent with previous studies (2, 8).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, subcutaneous administration of ONO-1301 significantly attenuated bleomycin-induced increases in total cell counts, neutrophil counts, and total protein level in BAL fluid. Earlier studies have shown that TXA 2 acts as a proinflammatory mediator via enhancement of pulmonary vascular permeability (18,24) and neutrophil adhesion (33). In the present study, TXB 2 , a stable metabolite of TXA 2 , was significantly increased after bleomycin injection, which is consistent with previous studies (2, 8).…”
Section: Discussionsupporting
confidence: 83%
“…Leukotrienes, potent chemoattractants and coactivators of neutrophils 22 are increased in bronchial fluid and serum of patients with ARDS, but appear to have no predictive value for the development of ARDS. 10 Our study appeared to confirm this finding as no significant changes in serum LTB 4 were found in any patient during the intraoperative and early postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane is known to stimulate CD18 facilitated adhesion of neutrophils to pulmonary endothelial cells much more than to other endothelial cells. 22 This may lead subsequently to leucocyte margination, sequestration, adhesion, capillary leakage and pulmonary oedema. Furthermore, thromboxane is a potent vasoconstrictor and procoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…TXA 2 , an important lipid mediator of platelets, is involved in platelet-neutrophil interactions (41) and plays a critical role in acid-induced ALI (7,42). TXA 2 induces increased permeability (42) and PMN adhesion to pulmonary endothelial cells (43). TP blocking or thromboxane synthesis inhibition was previously shown to protect from acidinduced PMN sequestration and protein leakage (42,44).…”
Section: Figurementioning
confidence: 99%